PENINGKATAN PROSES DAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V: Proses dan Hasil Belajar IPS, Model Problem Based Learning - Azhari, Fitria; Sabir, Arisman; -, subhanadri (Jurnal Tunas Pendidikan, 2023)
This study aims to determine the effect of the Problem Based Learning model on social studies learning processes and outcomes in fifth grade students at SDN 104/VI ​​Rantau Panjang VIII. The type of research conducted was classroom action research, the research subjects were all students of class V at SDN 104/VI ​​Rantau Panjang VIII, totaling 16 students. Data collection techniques using observation, learning achievement test sheets, and documentation. The analysis technique used is a qualitative and quantitative approach. The results of this research using the Problem Based Learning model show an increase in each cycle for the results of educator observations in cycle I with an average of 74.99% in the Good category and in cycle II of 85.71% in the Very Good category. The results of observations of students in cycle I with an average of 59.37% in the Poor category and cycle II of 81.25% in the Very Good category. While classical completeness in cycle I obtained an average value of student learning outcomes of 56.25% increasing to 87.5% in cycle II. Based on these data, it shows that the use of the Problem Based Learning model can improve social studies learning processes and outcomes in class V SDN 104/VI ​​​​Rantau Panjang VIII.